2015
DOI: 10.12703/p7-56
|View full text |Cite
|
Sign up to set email alerts
|

The search for novel analgesics: targets and mechanisms

Abstract: The management of the pain state is of great therapeutic relevance to virtually every medical specialty. Failure to manage its expression has deleterious consequence to the well-being of the organism. An understanding of the complex biology of the mechanisms underlying the processing of nociceptive information provides an important pathway towards development of novel and robust therapeutics. Importantly, preclinical models have been of considerable use in determining the linkage between mechanism and the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 423 publications
(393 reference statements)
1
73
0
2
Order By: Relevance
“…5) Opioid analgesics, antidepressants, anti-arrhythmic agents, or antiepileptic drugs may be used for the treatment of neuropathic pain. [6][7][8][9] In the present case, the major painful site was the right dorsal region and consistent with that of the treated collaterals. We first thought the category of the present patient's pain might be vascular pain because the characteristics of the pain (pulsatile, dull, and worsened with breath) seemed to be that of visceral pain belonging to nociceptive pain rather than neuropathic pain.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…5) Opioid analgesics, antidepressants, anti-arrhythmic agents, or antiepileptic drugs may be used for the treatment of neuropathic pain. [6][7][8][9] In the present case, the major painful site was the right dorsal region and consistent with that of the treated collaterals. We first thought the category of the present patient's pain might be vascular pain because the characteristics of the pain (pulsatile, dull, and worsened with breath) seemed to be that of visceral pain belonging to nociceptive pain rather than neuropathic pain.…”
Section: Discussionsupporting
confidence: 87%
“…6,7) Neuropathic pain arises from abnormal neural activity secondary to disease, injury, or dysfunction of the nervous system (eg, disk herniation, carpal canal syndrome, trigeminal neuralgia, or diabetic neuropathy). 5) Opioid analgesics, antidepressants, anti-arrhythmic agents, or antiepileptic drugs may be used for the treatment of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…The resident glial and migrating cells (T cells, macrophages and neutrophils) in the spinal cord along with the second-order neurons are activated by the release of these substances, which in turn release a collection of pro-inflammatory and anti-inflammatory molecules to further act on the secondorder neurons activating several protein kinases responsible for the phosphorylation of several membrane bound receptors, thus initiating and maintaining the hyperexcitable state of these neurons, and further sending the nociceptive signals to higher brain centres. The second-order neurons facilitate the excitability of dorsal horn projection neurons and scheme onto raphespinal serotonergic neurons through the bulbospinal pathway which dismiss in dorsal horn neurons [24]. In Table 2, central and peripheral pain targets are shown along with their source of cell insult/stimuli and inflammatory mediators and receptors which are and may be the future targets for pain alleviation.…”
Section: Central Targetsmentioning
confidence: 99%
“…Although the source of the pain state may be distinguishable, many clinical pain states likely reflect a combination of mechanisms; and, increasing evidence has pointed to overlapping components at the level of the primary afferent and spinal dorsal horn. These mechanisms and their associated pharmacology and biology have been extensively reviewed elsewhere [10,11]. In this discussion we will focus on the lumbar intrathecal route of drug delivery and consider: i) ongoing developments in the pharmacology of spinal therapeutics focusing on agents/targets that have been employed and shown to a varying degree to have efficacy in humans, ii) novel targeting methodologies and iii) several issues relevant to intrathecal drug delivery.…”
Section: A R T I C L E H I S T O R Ymentioning
confidence: 99%
“…It should be stressed that virtually all of the mechanistic studies defining pain processing have shown the importance of spinal systems. Accordingly, future pharmaceutical targets may likely arise from one or more of systems that have been shown to have actions on the behaviorally defined pain end point after intrathecal delivery in one of more preclinical models (see [10][11]). Several of these will be summarized below.…”
Section: Other Potential Pharmacological Spinal Targetsmentioning
confidence: 99%